The Ju/'hoan San of Nyae Nyae and Namibian independence : development, democracy, and indigenous voices in Southern Africa /: development, democracy, and indigenous voices in Southern Africa. (2011) - Biesele, Megan; Hitchcock, Robert K
No abstract available